Comparative Analysis of the Nutritional and Anti-nutritional Compositions of Mango (Mangifera indica), Pawpaw (Carica papaya) and Pineapple (Ananas comosus) Sold in Lafia Modern Market, Nigeria (Lafia Journal of Scientific and Industrial Research, 2025)
The study examined the nutrition and anti–nutritional compositions of mango, pawpaw and pineapple using standard analytical techniques. The result of proximate composition showed that mango has higher fat, ash, crude fibre, moisture, carbohydrate, fatty acid and energy contents than pawpaw and pineapple, while pawpaw has higher crude protein value than mango and pineapple. The antinutrient composition of the samples revealed that pineapple has higher oxalate, alkaloids, tannins and phytate than mango and pawpaw. The results of amino acid composition revealed that Leucine was the most concentrated essential amino acid (EAA) in mango, pawpaw and pineapple, with the values of 4. 61, 5.02 and 5.60 g/100 g cp respectively. It was also found that Tryptophan was the least concentrated essential amino acid in the three samples with a value of 0.84, 0.92 and 0.63 g/l00 g in mango, pawpaw and pineapple, respectively. The calculated isoelectric points (pI) for mango, pawpaw and pineapple fruits were 6.09, 6.83 and 5.97, respectively. The P–PER values were 1.83, 1.67 and 1.80 for the mango, pawpaw and pineapple fruit samples, respectively. The study revealed that the three fruits were good sources of nutrients needed by the body and were low in anti-nutrients. Their consumption is highly recommended.